Sistem Pendidikan Nasional Berdasarkan Tauhid - Hafiedh Hasan (Madaniyah, 2014)
National Education is education that is rooted in the nation's culture and is based on Pancasila and the 1945 Constitution. The aim is to educate the life of the nation and develop Indonesian people as a whole. In the 1999 GBHN the three main missions of the national education system were written, which turned out to be out of target. Most of the students graduating from schools who are now believed by the people to govern the country have a bad character, causing our country to experience a setback as it is today. Even students who have not yet graduated have some negative attitudes such as fighting, using and selling drugs, fighting teachers and parents, damaging public facilities and so on. Other failures are seen in the quality of Indonesian students whose abilities are far behind compared to students from the country and Indonesian graduation standards that are far from international standards. Monotheism-based education is one of the solutions for education in Indonesia, monotheism-based education is the whole educational activity which includes guidance, coaching and development of human potential in accordance with their talents, abilities and expertise that originates and leads to God, Allah SWT. Furthermore, the knowledge and expertise that has been applied in life as a realization of the cocret of devotion and obedience to God. Efforts in that direction were initiated by instilling the values ​​of the morality of al-karimah (manners, manners, (according to our local terminology in Indonesia) in each student and then later implemented through the role of the Caliphate as a prosperous and life preserver in this world. Tawheed Based Curriculum is implementing an educational curriculum whose content and learning methods lead to the formation of Islamic character to increase devotion to Allah SWT, and more principle in the KBT will present God in all subject matter studied by students so there is no separation between religion and life. Life in the world is a means of achieving success in the hereafter, hereafter is the control of our lives in the world.